The Urgency of Education and Training Approaches and Methods for PAI Teacher Professionalism in the Era of Society 5.0 - Rahmawati; Ali Nurhadi; Mahfida Inayati (al-Afkar, Journal For Islamic Studies, 2024)
The era of society 5.0, a technology-based era that makes humans part of it, means that internet access is no longer used only to share news or information, but, it has gone hand in hand with human life. Method with qualitative approach through type of library research. Continuing to data collection techniques using text reading techniques, classification and analysis in the form of content analysis. The results of efforts to improve the professional of PAI teachers in the 5.0 era through heutagogy approaches and Internet of Things (IoT) methods. As for the context of PAI teachers and the era of Society 5.0, heutagogy is important for several reasons: Deep understanding and personalization of learning, dealing with information complexity, increasing critical and creative thinking skills, student independence, technology-based skill development, alignment with Islamic values and ethics, development of lifelong learning attitudes and contextual and multicultural understanding. Meanwhile, the application of the Internet of Things (IoT) Method in training for Islamic Religious Education (PAI) teachers in the era of Society 5.0: Interactive learning, monitoring the learning process, adapting learning materials, accessing learning materials remotely, monitoring student welfare, virtual collaboration, utilizing smart devices, data analysis for improvement and IoT-based professional training. Thus, the application of heutagogy approaches and IoT methods in training for PAI teachers can help to adapt to the demands of the Society 5.0 era, utilize technology effectively, and improve the quality of learning and professionalism and offer various opportunities to improve learning and teaching.